The Effectiveness of AI Chatbots in Business - SPIVAKOVSKYY, Sergiy; DANILEVIČA, Alina; SAMCHUK, Volodymyr; FOMIN, A. S.; MILONUSHKIN, Kostyantin (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025DO - 10.14505/tpref.v16.3(35).08, 2025)
Against the backdrop of digital business transformation, the present article delves into the efficacy of AI chatbots as a mechanism for enhancing sales on social media platforms. The relevance of this study is underscored by the rapid expansion of e-commerce and the imperative to refine marketing channels to sustain competitive advantage within the digital landscape. The purpose of the research is to quantify the chatbots’ influence on key business metrics and to form an integral effectiveness index of their implementation. The methodology employed involves the calculation of an Integral Efficiency Index (IEI) through the application of weighting factors, normalization of business indicators to unify their scale, and the utilization of quantitative analysis alongside mathematical modeling techniques to interpret the results obtained. The study findings reveal that the use of AI chatbots leads to a 67% increase in sales, a 55% increase in qualified leads, and a 61% increase in staff productivity. The Integral Efficiency Index stands at 56.825%, signifying a substantial degree of synergy among the various components of efficiency. This study indicates that chatbots effectiveness is contingent upon the technology utilized and their integration within a company's operational processes. The developed IEI methodology facilitates a quantitative evaluation of chatbot implementation efficacy while also identifying growth areas for further technological interventions. The scientific novelty of the study lies in the development and testing of an integral index of AI chatbot effectiveness for a comprehensive assessment of the impact of technology on business processes.